Risk Factors for Vaginal Discharge in Adolescent Girls - Salina, Salina; Arlina, Andi; Khairat, Nur Ummul (Advances in Healthcare Research, 2025)
Purpose: This study aims to examine the risk factors contributing to abnormal vaginal discharge in adolescent girls by integrating biological, hygienic, socio-cultural, economic, and psychological determinants. Unlike previous research on hormonal influences, this study offers a comprehensive perspective on how various factors affect adolescent reproductive health. Research Design and Methodology: This research employs a systematic literature review (SLR) approach to synthesize findings from scholarly articles published after 2018. Relevant studies were retrieved from Elsevier, Emerald, Wiley, and Springer databases. The analysis focuses on identifying dominant biological, behavioral, and environmental factors contributing to vaginal discharge among adolescent girls, along with potential interventions to mitigate health risks. Findings and Discussion: The results indicate that hormonal fluctuations during puberty influence vaginal microbiota and secretion levels, while poor hygiene practices, lack of reproductive health education, and socio-economic constraints exacerbate infection risks. Cultural stigmas surrounding menstruation and vaginal health further hinder adolescents from seeking timely medical attention. Additionally, stress and mental health issues contribute to hormonal imbalances, increasing susceptibility to abnormal discharge. These findings emphasize the interconnectedness of physiological, behavioral, and environmental factors in adolescent reproductive health. Implications: This study highlights the importance of comprehensive school reproductive health education, enhanced access to sanitary products, and reduced social stigmas through targeted public health campaigns. Policymakers should prioritize the affordability of sanitary products and ensure access to proper sanitation facilities, particularly in low-income communities. Future research should explore empirical approaches, including qualitative interviews and regional case studies, to further assess the lived experiences of adolescent girls in diverse cultural contexts.